The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/21541264.2017.1333558
|View full text |Cite
|
Sign up to set email alerts
|

Sub1 and RNAPII, until termination does them part

Abstract: Sub1 was initially identified as a coactivator factor with a role during transcription initiation. However, over the last years, many evidences showed that it influences processes downstream during mRNA biogenesis, such as elongation, termination, and RNAPII phosphorylation. The recent discover that Sub1 directly interacts with the RNAPII stalk adds new insights into how it achieves all these tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The human positive cofactor 4 (PC4) or Sub1 in yeast has recently attracted great attention of researchers worldwide (F. Liao et al, 2020; Mondal et al, 2019; Sikder et al, 2019). PC4 has been considered as an evolutionarily conserved transcriptional co‐activator since the first identification (Ge & Roeder, 1994), which is involved in transcriptional activation (Calvo, 2018), oxidative stress (Yu et al, 2016) histone modification (Sikder et al, 2019), and maintaining genomic stability (Garavis & Calvo, 2017). In this study, for the first time, we find that PC4 is increased and becomes activated with age, and transgenic expression of PC4 disturbs mTOR‐regulated proteostasis and causes global accelerated ageing by promoting histone acetylation.…”
Section: Introductionmentioning
confidence: 99%
“…The human positive cofactor 4 (PC4) or Sub1 in yeast has recently attracted great attention of researchers worldwide (F. Liao et al, 2020; Mondal et al, 2019; Sikder et al, 2019). PC4 has been considered as an evolutionarily conserved transcriptional co‐activator since the first identification (Ge & Roeder, 1994), which is involved in transcriptional activation (Calvo, 2018), oxidative stress (Yu et al, 2016) histone modification (Sikder et al, 2019), and maintaining genomic stability (Garavis & Calvo, 2017). In this study, for the first time, we find that PC4 is increased and becomes activated with age, and transgenic expression of PC4 disturbs mTOR‐regulated proteostasis and causes global accelerated ageing by promoting histone acetylation.…”
Section: Introductionmentioning
confidence: 99%
“…Sub1, a conserved factor (yeast homolog of mammalian PC4) was previously found to facilitate Pol II transcription in a variety of ways ( Garavís and Calvo, 2017 ; Calvo, 2018 ), to be recruited to the PIC ( Sikorski et al, 2011 ), and to alter accessibility of promoter single-stranded DNA, consistent with initiation functions ( Lada et al, 2015 ). sub1∆ has extensive genetic interactions with initiation factors and itself causes TSSs to shift downstream ( Wu et al, 1999 ; Knaus et al, 1996 ; Braberg et al, 2013 ; Koyama et al, 2008 ), though its actual role in initiation is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, double mutants shifted ADH1 TSS distributions to similar extent as the tfg2∆146-180 single mutant (Figure 7C, Figure 7 -Figure supplement 1) as predicted for an increase in initiation efficiency buffering against effects of increase in scanning processivity. Sub1, a conserved factor (yeast homolog of mammalian PC4) was previously found to facilitate Pol II transcription in a variety of ways 70,71 , to be recruited to the PIC 72 , and to alter accessibility of promoter single-stranded DNA, consistent with initiation functions 73 . sub1∆ has extensive genetic interactions with initiation factors and itself causes TSSs to shift downstream 29,38,50,74 , though its actual role in initiation is unknown.…”
Section: Genetic Interactions Between Initiation Factors and Ssl2 Alleles Suggest Distinct Roles For Ssl2 And Other Factors In Tss Scannimentioning
confidence: 99%
“…Sub1, a conserved factor (yeast homolog of mammalian PC4) was previously found to facilitate Pol II transcription in a variety of ways 70, 71 , to be recruited to the PIC 72 , and to alter accessibility of promoter single-stranded DNA, consistent with initiation functions 73 . sub1 Δ has extensive genetic interactions with initiation factors and itself causes TSSs to shift downstream 29, 38, 50, 74 , We found sub1 Δ to confer a His + phenotype for the imd2Δ::HIS3 initiation reporter 41 and furthermore found that Pol II GOF alleles appeared epistatic to sub1 Δ, leading to the proposal that sub1 Δ effects in initiation were distinct from TFIIB or TFIIF alleles 39 .…”
Section: Resultsmentioning
confidence: 99%